2020
DOI: 10.1371/journal.pone.0227021
|View full text |Cite
|
Sign up to set email alerts
|

Percent amplitude of fluctuation: A simple measure for resting-state fMRI signal at single voxel level

Abstract: The amplitude of low-frequency fluctuation (ALFF) measures resting-state functional magnetic resonance imaging (RS-fMRI) signal of each voxel. However, the unit of blood oxygenation level-dependent (BOLD) signal is arbitrary and hence ALFF is sensitive to the scale of raw signal. A well-accepted standardization procedure is to divide each voxel's ALFF by the global mean ALFF, named mALFF. Although fractional ALFF (fALFF), a ratio of the ALFF to the total amplitude within the full frequency band, offers possibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
116
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 43 publications
3
116
1
Order By: Relevance
“…In the slow‐3 band, PerAF decreased in the frontal lobe and limbic system. PerAF is an indicator that reflects the percentage fluctuation of rs‐fMRI and has good repeatability 14 . According to our results, PerAF may be more suitable for analysis in slow‐3.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the slow‐3 band, PerAF decreased in the frontal lobe and limbic system. PerAF is an indicator that reflects the percentage fluctuation of rs‐fMRI and has good repeatability 14 . According to our results, PerAF may be more suitable for analysis in slow‐3.…”
Section: Discussionsupporting
confidence: 51%
“…Local functional indicators of rs‐fMRI can evaluate spontaneous neural activity from different aspects. The amplitude of low‐frequency fluctuation (ALFF), fractional amplitude of low‐frequency fluctuation (fALFF), percent amplitude of fluctuation (PerAF), and wavelet‐based amplitude of low‐frequency fluctuation (Wavelet‐ALFF) 14,15 can describe the amplitude of local spontaneous nerve activity. Regional homogeneity (ReHo) can describe the consistency of spontaneous neural activity in local brain regions and adjacent brain regions 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…It directly characterizes the local spontaneous brain activity at the voxel level at resting state [Zang et al, 2007]. Compared with another index named fractional ALFF (fALFF), which also characterizes the local spontaneous brain activity, ALFF has shown higher test–retest reliability [Jia et al, 2020]. Previous studies have shown atypical regional ALFF in ASD [Guo et al, 2017; Lu et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Although rs-fMRI lacks a clear control design, the percentage of BOLD signal intensities relative to the average BOLD signal intensity at each time point is measured and the average value is obtained in the whole time series, which is the “percent amplitude of fluctuation” or PerAF. 12 PerAF could be further standardized by global mean PerAF, ie, mPerAF. The mPerAF has two stages of standardization, the first is the percentage of fluctuation amplitude at the single voxel or signal time series level.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, mPerAF can correct the change caused by the difference of relative BOLD signal strength. 12 Some studies have shown that PerAF shows similar scanner internal reliability as ALFF, but with reduced influence of the BOLD signal strength, and it can become a higher reliability index than ALFF, ReHo, and degree centrality (DC). 11 Therefore, PerAF has great potential in voxel whole-brain analysis.…”
Section: Introductionmentioning
confidence: 99%